2016
DOI: 10.1097/mbc.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of an acute spinal epidural hemorrhage in a child with hemophilia a with inhibitor

Abstract: Hemophilia A is an inherited, X-linked, recessive disorder caused by deficiency of clotting factor VIII. Central nervous system hemorrhage is an uncommon complication in patients with hemophilia. We report the case of a 5-year-old child who had intraspinal hematoma with nonsurgical, conservative management. It should be kept in mind that the optimal management is decided according to patient's condition because of high morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We excluded from the analysis one case of hemophilia B [15] and one with acquired hemophilia [16]. We included a total of 12 cases of patients diagnosed with hemophilia A that reported inhibitor presence from 1993 to date [17][18][19][20][21][22][23][24][25][26]. Most of these 12 patients had severe hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded from the analysis one case of hemophilia B [15] and one with acquired hemophilia [16]. We included a total of 12 cases of patients diagnosed with hemophilia A that reported inhibitor presence from 1993 to date [17][18][19][20][21][22][23][24][25][26]. Most of these 12 patients had severe hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Oymak et al 4 also successfully treated an infant with severe hemophilia A and inhibitors who presented with an SEH using recombinant activated factor VIIa. Erkutlu et al 5 reported the successful treatment of a 5-year-old child with an SEH using activated PCCs (aPCCs).…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous case reports have identified only 8 cases of atraumatic spinal hematoma leading to a diagnosis of hemophilia (Table 1), and between 1848 and 2015, an additional 35 published cases of spinal epidural hematoma in pediatric hemophilia patients. 8,[10][11][12][13] The presenting complaints of the atraumatic patients varied, but all included neurological findings of weakness or urinary/ bowel symptoms. [2][3][4][5][6][7][8][9] The cause of atraumatic spinal epidural hematoma in both hemophiliac and nonhemophiliac patients is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…Known maternal carrier status, followed by bleeding events, was the most common reason for diagnosis 1 . Previous case reports have identified only 8 cases of atraumatic spinal hematoma leading to a diagnosis of hemophilia (Table 1), and between 1848 and 2015, an additional 35 published cases of spinal epidural hematoma in pediatric hemophilia patients 8,10–13 . The presenting complaints of the atraumatic patients varied, but all included neurological findings of weakness or urinary/bowel symptoms 2–9 …”
Section: Discussionmentioning
confidence: 99%